Towards A Liberating Eschatology. Imagining The End Of The World To Survive The “Horrors Of The Anthropocene” - Gagos, Fabrice (2022)
First examining how capitalist realism and capitalist sorcery are suppressing the ability to think new futures through the manufacturing of what Pignarre and Stengers call infernal alternatives and how the fear of such alternatives limit the influence of tools such as the IPCC reports and the media in acknowledging the need for capitalism to be challenged in regards of climate change, this essay is an attempt to help ‘breaking the spell’, the common thought that ‘it is easier to imagine the end of the world than the end of capitalism’.